3D Culture of Tonsil‐Derived Mesenchymal Stem Cells in Poly(ethylene glycol)‐Poly(l‐alanine‐co‐l‐phenyl alanine) Thermogel. Issue 11 (24th June 2014) - Park, Min Hee; Yu, Yeonsil; Moon, Hyo Jung; Ko, Du Young; Kim, Han Su; Lee, Hyukjin; Ryu, Kyung Ha; Jeong, Byeongmoon
<x xml:space="preserve">Abstract</x> Poly(ethylene glycol)‐poly(l‐alanine‐co‐l‐phenyl alanine) (PEG‐PAF) aqueous solutions undergo sol‐to‐gel transition as the temperature increases. The transition is driven by the micelle aggregation involving the partial dehydration of the PEG block and the partial increase in β‐sheet content of the PAF block. Tonsil‐tissue‐derived mesenchymal stem cells (TMSCs), a new stem cell resource, are encapsulated through the sol‐to‐gel transition of the TMSC‐suspended PEG‐PAF aqueous solutions. The encapsulated TMSCs are in vitro 3D cultured by using induction media supplemented with adipogenic, osteogenic, or chondrogenic factors, where the TMSCs preferentially undergo chondrogenesis with high expressions of type II collagen and sulfated glycosaminoglycan. As a feasibility study of the PEG‐PAF thermogel for injectable tissue engineering, the TMSCs encapsulated in hydrogels are implanted in the subcutaneous layer of mice by injecting the TMSC suspended PEG‐PAF aqueous solution. The in vivo studies also prove that TMSCs undergo chondrogenesis with high expression of the chondrogenic biomarkers. This study suggests that the TMSCs can be an excellent resource of MSCs, and the thermogelling PEG‐PAF is a promising injectable tissue engineering scaffold, particularly for chondrogenic differentiation of the stem cells.